Introduction to the Journal - Pawłowski, Artur (Problemy Ekorozwoju, 2006)
The concept of sustainable development was formulated at a time when modern man had technical means to transform virtually any world. At the same time, he gets lost for the purposes that these transformations are to serve. For many years, technical power has been sufficient to completely destroy the biosphere, and if it does not, the real and close perspective is the depletion of fossil fuel resources and other raw materials. In addition, globally the condition of the natural environment is constantly deteriorating (although some improvement can be observed locally). At the same time, the disparity between poor and rich countries is growing. Although global food production is high enough for everyone, millions of people are still starving. Social conflicts are also escalating, often due to poverty. Increasing automation leads to the expansion of the unemployment and entails the creation of a group of unnecessary people, living on the margins of modern civilization and gradually excluded from it. Already these selected challenges show how complicated and difficult the situation of the modern world is. Can the visible crisis be overcome? For this to happen, the concept of sustainable development was formulated. This is not just another environmental protection program, the perspective of necessary actions is much broader. The voice of naturalists is still important, but the reasons for philosophical, economic and technical sciences must also be taken into account. We are giving the reader the new issue of a magazine devoted to the issues of sustainable development and eco-philosophy. We have already managed to gather around this initiative a significant group of outstanding scientists, but this is only the beginning of the road. The papers presented in this issue introduce the process of shaping eco-philosophical thought (both in the international perspective and in the context of the work of Polish authors), which enabled the formulation of the principle of sustainable development. We also introduce the concept of multidimensionality of sustainable development, integrating various fields of human activity. At the same time, we pay attention to the important problems of the modern world: the consequences of rapidly changing changes (the vision of the “turbo-world”) or the progressing processes of globalization. Looking for opportunities for improvement, we invite you to analyze problems related to the formation of ecological awareness. Whether the new publishing initiative will succeed – it depends on the readers. We invite you to cooperate and create this discussion forum together!